JEJAK BUDDHISME DALAM NOVEL KARYA KWEE TEK HOAY “BOENGA ROOS DARI TJIKEMBANG”: PERSPEKTIF FENOMENOLOGI - Yulianti Yulianti (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2017)
In the first half of the 20th century, many Buddhist background texts were published, primarily by private publishers. One of the scriptwriters was a Chinese Peranakan named Kwee Tek Hoay (KTH). As a Chinese philosopher and philosopher, KTH has written many short stories, novels, and translations in the field of kebatinan. The article attempts to investigate Buddhism, especially Buddhist phenomena with a phenomenological paradigm in one of the KTH works entitled Boenga Roes from Tjikembang.